The Psychopathology of Basal Ganglia Calcification - Michael P. Philpot; Shon W. Lewis (Behavioural Neurology)
Basal ganglia calcification (BGC) was found in 36 of 4122 patients undergoing computed tomography as part of a clinical investigation of their psychiatric illness. The prevalence of BGC increased with age in both men and women. No psychiatric diagnosis was specifically associated with BGC although calcification of the putamen and the caudate was only found in patients with functional disorders. No abnormalities of calcium or phosphate metabolism were found. The results do not support the hypothesis that BGC is an aetiological factor in schizophrenia-like psychoses.